Endobronchial Therapy With Gentamicin and Dexamethasone After Airway Clearance by Bronchoscopy in Exacerbation of Non-Cystic Fibrosis Bronchiectasis: A Real-World Observational Study - Li, Qiuhong; Huang, Beijie; Gu, Hongyan; Zhou, Ying; Shan, Xizheng; Meng, Siming; Qin, Meng; Shi, Jingyun; Chen, Yanan; Li, Huiping (Frontiers in Pharmacology, 2021)
Background：The exacerbation of non-cystic fibrosis bronchiectasis (NCFB) may lead to poor prognosis. The objective of the study was to retrospectively analyze the clinical efficacy and safety of endobronchial therapy with gentamicin and dexamethasone after airway clearance by bronchoscopy in exacerbation of NCFB. Methods: We retrospectively reviewed 2156 patients with NCFB between January 2015 and June 2016, and 367 consecutive patients with exacerbation of bronchiectasis who had complete data and underwent airway clearance (AC) by bronchoscopy. The final cohort included 181 cases of intratracheal instillation with gentamicin and dexamethasone after AC (a group with airway drugs, named Drug group) and 186 cases of AC only (a group without airway drugs, named Control group). The last follow-up was on June 30, 2017. Results: The total cough score and the total symptom score in the Drug group were improved compared to the Control group during exacerbation and three months after discharge (P<0.001). Re-examination of chest HRCT within 4-6 months after discharge revealed that the extent of mucous plugging, collapse/consolidation, and the Bhalla score were all significantly improved in the Drug group. Moreover, the re-exacerbations in the Drug group were significantly decreased within one year after discharge. Univariate analysis showed a highly significant prolongation of the time to first re-exacerbation in bronchiectasis due to treatment with airway drugs compared without. Multivariate Cox regression analysis showed that the risk of first re-exacerbation in the Drug group decreased by 29.7% compared with the Control group. Conclusions: Endobronchial therapy with gentamicin and dexamethasone after airway clearance by bronchoscopy is a safe and effective method for NCFB.